Cure everyone and vaccinate the rest: The patient perspective on future hepatitis B treatment. Issue 11 (11th August 2021) - Freeland, Catherine; Racho, Rhea; Kamischke, Maureen; Moraras, Kate; Wang, Evangeline; Cohen, Chari
Abstract: Those living with chronic hepatitis B virus (HBV) require years, if not decades, of regular monitoring to prevent liver complications from occurring. An estimated 292 million people were living with chronic HBV globally in 2018 with approximately 2.4 million of those residing within the United States (US). This study is one of the first of its kind that aims to explore the treatment preferences for those living with chronic HBV through qualitative interviews. Participant data were collected by in‐depth telephone interviews using a semi‐structured discussion guide. A codebook guided the organization of data, and codes were developed by review of the literature ( a priori ) and through line‐by‐line reading of a subsample of queries. All data transcripts (N = 19) were independently double coded. Overarching themes identified from the data specific to the treatment modalities and implications of a functional HBV cure included the concern about side effects, treatment modality, frequency, duration, cost‐effectiveness and overall impact on their lives. Qualitative data analysis revealed the significant impact that an HBV functional cure would have on quality of life. Benefits of a cure were described as not having a finite course of treatment, improving overall vitality, and reducing the fear and anxiety associated with lifelong infection and potential development of liver cancer. Many individuals expressed the desire for a cure for HBV, stating it would be life‐changing, and a 'miracle'. As new therapies are in development, more research should examine in detail the treatment preferences of those living with HBV.